LOS USHNUS SOBRE HUACAS LOCALES: ANÁLISIS PRELIMINAR DE LOS USHNUS DEL DISTRITO DE OCROS, AYACUCHO - García Reyes, Anuor Abel (2017)
This research consists of a morpho- functional analysis of isolates ushnus that are on huacas or apus of local importance, called Pumaqawanqa and Huayna Pizarro. The purpose is to contribute to knowledge about the geographical and symbolic characteristics that have influenced for the installation of ushnus isolated in the geographical area Ocros district, its relationship with the immediate environment and the activities that took place in them. Also, understand the strategy of the Incas in establishing these structures on local deities, their supremacy to local groups such as a theme to explain the incorporation of the territory Chanca under the power of Tahuantinsuyo. In the ayacuchano territory the presence of ushnus have been classified according to the geographical, such as context: in the main squares in dairy farms in the vicinity of the sanctuaries, on top of local huacas, in the main open and in the vicinity of the campus chaccu vicuna (Cavero 2015). Finally, we will focus on the type of Huayna Pizarro site, one of the sites of Inca influence amid settlements Chanca and in poor condition.